The Effect of Profitability and Leverage on Tax Avoidance in Manufacturing Companies Listed on the Indonesia Stock Exchange (Food and Beverage Industry Sub-Sector for the 2019-2023 Period) - Alda, Yuli; Mulyani, Sri; Nuridah, Siti (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study is to find out how much profitability and leverage affect tax avoidance in manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. The sampling technique in this study uses purposive sampling. Based on the criteria that have been determined, as many as 18 companies were obtained. The analysis method used is multiple linear regression with t test (Partial), F test (Simultaneous) and R-Square test (Coefficient of Determination). The results of the study partially show that profitability does not have a significant effect on tax avoidance, leverage also does not have a significant effect on tax avoidance and simultaneously profitability and leverage have no effect on tax avoidance.